FORMATION OF THE MANAGEMENT SYSTEM AT TASSR 1918-1924 - Abdullayev Yo'ldosh (The Conference Hub, 2025)
In the 5th Congress of Turkestan Oka Soviets (April 20—may 1, 1918), on April 30, the Russian Soviet Federation was founded under the name Turkestan Soviet republic. The Supreme bodies of S'yezdsa: the Central Executive Committee of the Republic of Turkestan (Turkestan MI K) and the Soviet of people's commissars of the Republic of Turkestan (Turkestan ISS) were formed. The TCP was divided from the administrative district into the provinces of Fergana, Samarkand, Syrdarya, Yettisuv, Zakaspiy, and later Amudarya (Turkmen). The territory of the Republic was bordered by the states of the PRC, the PRC, the Kazakh ASSR, Afghanistan, Iran, China. The emergency 6th congress of Soviets of the Republic of Turkestan adopted the TCP Constitution on the template of the Constitution of the RSFSR. A new Constitution was adopted at 9s'ezd, renaming the TSR the Turkestan Soviet Socialist Republic (TSSR).